Decellularization of Porcine Carotid Arteries: From the Vessel to the High-Quality Scaffold in Five Hours - Massaro, Maria Stefania; Kochová, Petra; Pálek, Richard; Rosendorf, Jáchym; Červenková, Lenka; Dahmen, Uta; Liška, Václav; Moulisová, Vladimíra (Frontiers in Bioengineering and Biotechnology, 2022)
The use of biologically derived vessels as small diameter vascular grafts in vascular diseases is currently intensely studied. Vessel decellularization provides a biocompatible scaffold with very low immunogenicity that allows to avoid immunosuppression after transplantation. Good scaffold preservation is important as it facilitates successful cell repopulation. Also mechanical characteristics have to be carefully evaluated when the graft is intended to be used as an artery due to high pressures the vessel is subjected to. Here we present a new fast decellularization protocol for porcine carotid arteries followed by investigation of the quality of obtained vessel scaffolds in terms of maintenance of important extracellular matrix (ECM) components, mechanical resistance and compatibility with human endothelial cells. Our results evidence that our decellularization protocol minimally alters both the presence of scaffold proteins and its mechanical behavior and that human endothelial cells are able to adhere to the scaffold in vitro. We conclude that if a suitable protocol is used, a high quality decellularized arterial scaffold of non-human origin can be promptly obtained having a great potential to be recellularized and used as an arterial graft in transplantation medicine.